Using a tablet-mediated intervention for teaching pre-addition skills to children with autism - Gül Kahveci; Nergüz Bulut Serin; Osman Akkus (Intelektual Pustaka Media Utama, 2023)
Nowadays, tablets and their applications are part of the children’s daily lives. These digital educational activities can become a potent educational tool for efficient and effective in neurotypical as well as children with autism spectrum disorder (ASD). Tablets and their applications allow children to take advantage of new learning platforms and effectively learning through activities in learning domains, such as mathematics. In the present study representational-abstract sequencing instruction in the form of explicit instruction used with the help of mobile technologies. The aim of this study is to match the semi-concrete visual drawings with the correct abstract mathematical pre-addition expressions. Findings suggest using a tablet mediated intervention is effective teaching to match the semi-concrete visual drawing with the correct abstract mathematical expression. Implications for practice and future research are discussed.